Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm new to boolean algebra and having problems simplifying expressions with odd number terms,

Expressions such as:


A'B'C'D + A'B'CD + AB'C'D + AB'CD + ABC'D


A'BC + AB'C' + A'B'C' + AB'C + ABC

Here is my logic for both expressions:

A'B'C'D + A'B'CD + AB'C'D + AB'CD + ABC'D

A'B'D'(C+C') + AB'D(C+C') + ABC'D

A'B'D + AB'D + ABC'D

B'D(A'+A) + ABC'D


I never touch the last term, and I don't know what rule I'm missing. Same thing happens on the second expression:

A'BC + AB'C' + A'B'C' + AB'C + ABC

A'BC + B'C'(A+A') + AC(B'+B)

A'BC + B'C + AC

Again, one term untouched..

For 1. the result should be AC'D + B'D

For 2. the result should be B'C + BC + AC

I could maybe use Karnaugh maps but I also would like to understand the algebra logic.

share|cite|improve this question
up vote 1 down vote accepted

It’s not too hard to check the results after you know them:

$$\begin{align*}B'D+ABC'D&=(B'+ABC')D\\ &=(B'+AB'C'+ABC')D\\ &=\Big(B'+A(B'+B)C')\Big)D\\ &=(B'+AC')D\\ &=B'D+AC'D \end{align*}$$


$$\begin{align*}A'BC + B'C + AC&=B'C+(A'B+A)C\\ &=B'C+(A'B+A+AB)C\\ &=B'C+\Big(A+(A'+A)B\Big)C\\ &=B'C+(A+B)C\\ &=B'C+AC+BC\;. \end{align*}$$

That second one can be further simplified to $AC+C=C$, since $B'C+BC=(B'+B)C=C$.

In both calculations I used the absorption law: $B'=B'+AB'C'$ in the first, and $A=A+AB$ in the second.

When you have no more than three or four proposition letters, you may find Venn diagrams helpful.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.